Dakwah Online Melalui Media Sosial - Sudirman Tebba (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Dakwah through electronic media is more effective because it has a wider reach than print media and is more interesting because it has pictures and sound. Dakwah is even more developed when social media appears because its reach is wider than electronic media and can appear at any time for 24 hours. The purpose of this qualitative study using the literature study method is to describe how da'wah through social media is increasingly widespread in this digital era. The results obtained include that the guidelines for broadcasting behavior should contain religious, moral values and the unity of applicable laws; and other norms applicable and accepted by the general public and broadcasting institutions. Knowing the target public will be useful for developing a communication strategy that is right on target. Information is anything that helps us in constructing or exchanging views on life. Communication and da'wah are all things that must be analyzed as actions (not messages) that contain a possibility or alternative. And one method of da'wah that is constructive and capable of being a solution to problems in the social order of society is the bilhal da'wah model. Which literally means conveying Islamic teachings through real practices.Keywords: Online Dakwah; Social; Media AbstrakDakwah melalui media elektronik ini lebih efektif, karena jangkauannya lebih luas dari pada media cetak dan lebih menarik karena ada gambar dan suaranya. Dakwah lebih berkembang lagi ketika muncul media sosial, karena jangkauannya lebih luas dari pada media elektronik dan bisa muncul setiap saat selama 24 jam. Tujuan kajian kualitatif dengan metode studi literatur ini adalah untuk mendeskripsikan bagaimana dakwah melalui media sosial yang semakin marak di era digital ini. Hasil yang didapatkan antara lain bahwa pedoman perilaku penyiaran hendaknya mengandung nilai-nilai agama, moral dan persatuan perundang-undangan yang berlaku; dan norma-norma lain yang berlaku dan diterima masyarakat umum dan lembaga penyiaran. Mengetahui publik sasaran, akan berguna untuk menyusun strategi komunikasi yang tepat sasaran. Informasi adalah setiap hal yang membantu kita dalam menyusun atau menukar pandangan tentang kehidupan. Komunikasi dan dakwah adalah semua hal harus dianalisis sebagai tindakan (bukan pesan) yang mengandung sebuah kemungkinan atau alternatif. Dan salah satu metode dakwah yang konstruktif dan mampu menjadi solusi permasalahan dalam tatanan sosial masyarakat ialah model dakwah bilhal. Yang secara harfiah berarti menyampaikan ajaran Islam melalui amaliah nyata.Kata Kunci: Dakwah Online; Media; Sosial